2011
DOI: 10.1038/nrneph.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of CKD: the benefits, limitations and effects on prognosis

Abstract: The past decade has seen an increasing focus on chronic kidney disease (CKD) and its attendant complications, which has resulted in improved understanding of their impact on health-care resources. The early detection of CKD has been facilitated by the implementation of routine reporting of estimated glomerular filtration rates (eGFRs) and by education of primary care physicians on the implications of detecting a decreased eGFR with respect to patient safety as well as to cardiovascular and renal outcomes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 115 publications
(115 reference statements)
0
64
0
1
Order By: Relevance
“…Reliable data on AKI recovery have significant implications for planning nephrological follow-up [40][41][42], for comparative research, and for power calculations in future intervention studies. Our analysis suggests that, in order to be comparable, reports on recovery from AKI should provide detailed data on the included population (inclusion or exclusion of non-survivors, proportion of CKD), on the definition and severity of AKI, on the definition used for and the timing of recovery assessment, and on the handling of missing baseline creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable data on AKI recovery have significant implications for planning nephrological follow-up [40][41][42], for comparative research, and for power calculations in future intervention studies. Our analysis suggests that, in order to be comparable, reports on recovery from AKI should provide detailed data on the included population (inclusion or exclusion of non-survivors, proportion of CKD), on the definition and severity of AKI, on the definition used for and the timing of recovery assessment, and on the handling of missing baseline creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Studies have also shown that "targeting people with stage 4 CKD for appropriate disease management adds value in terms of delayed progression of disease, and improved blood pressure control and CVD ("cardiovascular disease") risk management." [4] Thus, identifying CKD at an early stage may help physicians enhance the longer-term outcomes of these patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2) While acute kidney injury (AKI) is a known risk factor for CKD progression, current methods of diagnosis, such as the measurement of serum creatinine, are unsatisfactory due to their delay in the diagnosis of kidney disease. (3) As serum creatinine is affected by filtration function, its rise reflects a significant, and often permanent, loss of functioning nephrons.…”
Section: Introductionmentioning
confidence: 99%